Insecticide resistance dynamics in Aedes mosquitoes in Ghana - Afrane, Y.A.; Sraku, I.K.; Owusu-Asenso, C.M.; et al. (Gigabyte, 2025)
Arboviral diseases such as dengue, chikungunya, Zika, and yellow fever are of increasing endemicity and public health concern in Africa. Understanding the spatial distribution and dynamics of insecticide resistance in the Aedes vector could guide effective control interventions. We conducted larval surveys and WHO adult susceptibility bioassays on emerged adults from January 2019 to December 2023 in Ghana. Bioassays revealed widespread resistance in Ae. aegypti to pyrethroids, with 33.8–88.8% mortality for deltamethrin and 65–89% for permethrin. Ae. aegypti from Paga, Takoradi, and Accra was susceptible to pirimiphos-methyl. Ae. vittatus exhibited confirmed or possible resistance to pyrethroids. Ae. albopictus was found susceptible to all insecticides tested. Genotyping of mosquitoes (n = 887) identified high allelic frequencies of the F1534C kdr mutation in the pyrethroid-resistant Ae. aegypti populations. These findings highlight widespread pyrethroid resistance in the Ghanaian Aedes populations driven primarily by target-site insensitivity, and emphasize the urgent need for evidence-based vector-management strategies.
Research Article
Keywords: Ecology; Biodiversity; Taxonomy